Exploration of second-hand apparel acquisition behaviors and barriers - Hiller Connell, Kim Y. (International Textile and Apparel Association, Inc., 2011)
Post-consumer textile waste, including garments discarded by the original owner, is an environmental issue. In 2006, 11.8 million tons of textiles entered the United States municipal solid waste stream, with only 1.81 million tons being recovered for recycling, a recovery rate of 15.3%. On a yearly basis, Americans throw away approximately 68 pounds of apparel and textile products per person. Although American consumers (primarily through charity and donation programs) do prevent approximately 1.25 million tons of textile products from entering the municipal waste stream on an annual basis, a large portion of discarded clothing becomes solid waste. Furthermore, it is estimated that only 40% of all donated apparel is actually sold as clothing to American consumers. There remains very little understanding of how to increase the number of new consumers acquiring apparel through second-hand sources. This is the knowledge gap this exploratory study begins to fill.
Keywords: Second-hand; Apparel; Acquisition; Consumer behavior